The Effectiveness of Promotional Tools in Making Covid-19 Vaccination a Success: Hypothesis Testing Methods for Changing Cochran's Version - Susdarwono, Endro Tri; Surahmadi, Surahmadi (CV. Rayyan Dwi Bharata, 2022)
This study aims to examine the effectiveness of promotional tools in the success of the Covid-19 vaccination. In this study, the approach used was quantitative. The quantitative approach method uses hypothesis testing on the Cochran version change. The hypothesis testing method against the Cochran change test was applied to more than two groups of data samples on a nominal value scale or dichotomous ordinal. Basically the testing of this hypothesis is carried out to ensure the presence or absence of significant differences between a number of pairs of frequencies or proportions. The conclusion of this study is a Q value of 3,578, a Q value smaller than the chi-square value in the table of 7.815. Because the Q value is smaller than the chi-square value in the table, the null hypothesis states that the four promotional tools in order to make the Covid-19 vaccination program a success do not have a significant difference in effectiveness. Under these conditions, television, radio, newspapers, and social media have the same level of effectiveness in supporting the promotion of the success of the Covid-19 vaccination program in Indonesia.